Analisis Coordination Time Interval Over Current Relay Distribusi Pengolahan Air Minum Berbasis IEEE STD. 242 - Muhammad Al Faatih; Joko Joko; Tri Rijanto (INDO PUBLISHING, 2026)
Electrical systems in Water Treatment Plants require reliable protection systems to ensure the continuity of equipment operation, particularly pump motors. Short-circuit faults can produce large fault currents that may damage equipment and disrupt operational processes. This study aims to analyze short-circuit currents and evaluate the coordination of Over Current Relays (OCR) in the electrical distribution system of IPAM based on the IEEE Std. 242 standard. The research was conducted by modeling the electrical system using ETAP software based on the single line diagram, transformer data, motor data, and existing relay settings. The analysis results show that the maximum short-circuit current on the 0.4 kV side ranges from 32,270–35, 850 A, while on the 20 kV side it is approximately 3,128 A. The Time Current Characteristic (TCC) curve indicates that the feeder relay operating time ranges from 0.02 to 0.07 seconds, with a Coordination Time Interval (CTI) of approximately 0.2–0.3 seconds, which complies with the IEEE 242 standard (0.2-0.4 seconds). These results indicate that the protection coordination system operates selectively and reliably